Risk factors for type 2 diabetes mellitus in adolescents: a systematic review and meta-analysis - Metta Lestari Utami; Welly Rustanto; Lucia Pudyastuti Retnaningtyas; Maria Goretti Marianti Purwanto (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
The prevalence of type 2 diabetes mellitus (T2DM) in adolescents worldwide has increased over the last three decades. Several clinical studies concerning risk factors for T2DM in adolescents were reported, however, the results varied and no systematic review of the studies are reported. This study aimed to systematically review the risk factors for T2DM in adolescents. Publications in English about adolescent with T2DM aged 10-19 yr and coexisting risk factors were searched in Medline and Cochrane. This systematic review and meta-analysis were in-line with MOOSE guidelines. Each publication was assessed the titles, abstracts, and full text, and then extracted the data, and assessed the risk of bias and evidence quality were conducted by 2 independent reviewer. Seven studies involving 52,779 adolescents were included in this review. Meta-analysis using a fixed effect model with the inverse variance method was conducted to calculate the odds ratio with 95% confidence intervals. Adolescents who smoke both actively and passively were at risk of 2.88 times (pooled OR 2.88; 95% CI 1.99-4.17; I² = 61%), the male gender was at risk of 1.31 times (pooled OR 1.31; 95% CI 1.09-1.57; I² = 0%), having parents with a history of T2DM was at risk of 2.48 times (pooled OR 2.48; 95% CI 1.83-3.36; I² = 82%), obesity was at risk of 1.28 times (pooled OR 1.28; 95% CI 1.15-1.43; I² = 57%), and hypertension was 1.14 times more likely to get T2DM than those who did not have risk factors. Hypercholesterolemia was not a risk factor for T2DM (pooled OR 1.00; 95% CI 0.95-1.05; I² = 0%). In conclusion, the main risk factor for T2DM in adolescents is smoking, followed by parental T2DM, male gender, obesity, and hypertension.